Diagnosing the reality of the dimensions of lean leadership An analytical diagnostic study of the opinions ofa sample of leaders at the University of Dohuk (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The current research aims to diagnose the dimensions of lean leadership represented by (culture of improvement, self-development, qualification, Gemba, Hoshin Kanri) at the University of Dohuk, adopting the questionnaire as the main tool for collecting data, and relying on the statistical program (SPSS, Var. 27) for Analyzing the data, which amounted to (153) respondents as a sample representing the administrative leadership in the organization under study, using statistical methods (percentage, arithmetic mean, standard deviation, coefficient of variation, and intensity of response), and a set of conclusions were reached that confirm the availability of these dimensions at varying levels in the researched organization, in addition to presenting proposals, the most important of which is the need to pay attention to adopting lean leadership in the dimensions most expressed in order to achieve the organization’s desired goals.